ORGANIZAÇÃO MILITAR, PODER DE MANDO E MOBILIZAÇÃO DE ESCRAVOS ARMANDOS NAS CONQUISTAS: A ATUAÇÃO DOS CORPOS DE ORDENANÇAS EM MINAS COLONIAL (Revista de História Regional, 2007)
The article intends to approach the operational structure of the Corpos de Ordenanças analysing theirorganizational and legislative bases. Approaching the case ofMinas Gerais, we will also try to analyze the character of thesecorps, their hierarchy, contingent and disposition of troops forthe district of Vila Rica, between 1735-1777. We also try todemonstrate the importance of the relationships that theseofficials established with the slaves for the structuring andenlargement of their command power, since this should beallowed by such social segments.